Preferences For Interior Public Spaces In Kuala Lumpur Shopping Malls - Fazle Moula, Fazilah (2009)

(untitled)
As users of shopping malls, people’s needs play an important role in designing shopping malls, as it is not only for the quality of its shops and hospitality that matter, but also the interior public space it provides. People carry out various activities in interior public spaces whereby these spaces are crucial for the comfort of the customers who come to the malls. Unfortunately, the trend in the Malaysian malls’ interior public spaces have not been as public spaces, as they are rather designed specifically for business spaces. It is therefore suggested that the interior public spaces at shopping malls be designed according to people’s needs and preferences. Thus, this study was carried out to investigate preferences of the Kuala Lumpur residents towards interior public spaces at shopping malls. For this, a survey was conducted on among 240 participants in Bukit Bintang, MidValley and Jalan Tunku Abdul Rahman in Kuala Lumpur. The major part of the survey was the photo-questionnaire of the interior public spaces at malls. Besides photo questionnaire, the survey also consists of questions to gauge the participants’ perceived importance of the interior landscape elements at the public spaces in malls. The results from the analysis indicated that interior public spaces at malls could be categorized into three dimensions, namely Business, Green and Seating Dimensions. Green Dimension refers to the dimension, which has the highest mean preference rating while Business Dimension is the dimension with the lowest mean preference rating. The analysis also revealed that seating places, public clocks, plants and water features are perceived as important interior landscape elements at the public spaces provided while artificial plants and business entities are perceived as less important than other interior landscape elements involved in this study. Based on the people’s preferences, the study also showed five significant findings: the interior space at shopping malls as a place for public to spend time, to utilize and to relax, people preferred green interior and water features, while coherence and legibility are two important preference factors for the interior public spaces at shopping malls. The fourth and final significant findings are the rejection of business entities at public spaces in malls and that the age of the people who visited these places did matter in designing these spaces.